Spin wave modes observation in YIG thin films with perpendicular magnetic anisotropy - Capku, Zurbiye; Yildiz, Fikret (Elsevier, 2021)
Magnetic insulating materials with perpendicular magnetic anisotropy bring an innovation to the existing spin-related technologies and magnonic applications. Yttrium iron garnet (YIG) stands out among other ferrimagnetic insulators due to its remarkable and unique properties. In this work, we represent perpendicular magnetic anisotropy (PMA) in relatively thick YIG films between 40 nm and 120 nm grown on Si (100) substrates. The strain at the interface of the Si substrate / YIG film promoted by the lattice mismatch resulted in a magnetic easy axis along the film normal. Excitation of standing spin wave modes within the films through ferromagnetic resonance was studied. Based on the ferromagnetic spectra, multiple spin wave modes were obtained in all films up to 120 nm. Spin wave modes along the lateral of the film originate from inhomogeneous confined magnetic regions on the film surface. Exchange stiffness constant of YIG films was estimated between 1.02 x 10(-9) and 5.12 x 10(-9) Oe.cm(2). We anticipate that these findings will bring up investment in advanced magnonics, insulator spintronics, and quantum information processing applications.
Keywords: Ferromagnetic Resonance (FMR); Perpendicular magnetic anisotropy (PMA); Spin waves (SW); Yttrium iron garnet (YIG)